Historical introgressions from a wild relative of modern cassava improved important traits and may be under balancing selection - Wolfe, M.D.; Bauchet, Guillaume J.; Chan, A.W.; Lozano, R.; Ramu, P.; Egesi, Chiedozie N.; Kawuki, R.S.; Kulakow, Peter A.; Rabbi, Ismail Y.; Jannink, Jean-Luc (Oxford University Press, 2019)
Introgression of alleles from wild relatives has often been adaptive in plant breeding. However, the significance of historical hybridization events in modern breeding is often not clear. Cassava (Manihot esculenta) is among the most important staple foods in the world, sustaining hundreds of millions of people in the tropics, especially in sub-Saharan Africa. Widespread genotyping makes cassava a model for clonally-propagated root and tuber crops in the developing world and provides an opportunity to study the modern benefits and consequences of historical introgression. We detected large introgressed M. glaziovii genome-segments in a collection of 2742 modern cassava landraces and elite germplasm, the legacy of 1930's era breeding to combat disease epidemics . African landraces and improved varieties were on average 3.8% (max 13.6% ) introgressed. Introgressions accounted for significant (mean 20% , max 56% ) portion of the heritability of tested traits. M. glaziovii alleles on the distal 10Mb of chr. 1 increased dry matter and root number. On chr. 4, introgressions in a 20Mb region improved harvest index and brown streak disease tolerance. We observed the introgression frequency on chr. 1 double over three cycles of selection and that later stage trials selectively excluded homozygotes from consideration as varieties. This indicates a heterozygous advantage of introgressions. However, we also found that maintaining large recombination-suppressed introgressions in the heterozygous state allowed the accumulation of deleterious mutations. We conclude that targeted recombination of introgressions would increase the efficiency of cassava breeding by allowing simultaneous fixation of beneficial alleles and purging of genetic load.